Impact of GAD65 and IA2 autoantibodies on islet allograft survival - Lemos, Joana R. N.; Poggioli, Raffaella; Ambut, Jonathan; Bozkurt, Nujen C.; Alvarez, Ana M.; Padilla, Nathalia; Vendrame, Francesco; Ricordi, Camillo; Baidal, David A.; Alejandro, Rodolfo (Frontiers in Clinical Diabetes and Healthcare, 2023)
Introduction: Islet transplantation (ITx) shows promise in treating T1D, but the role of islet autoantibodies on graft survival has not been clearly elucidated. We aimed to analyze the effect of GAD65 and IA2 autoantibody status on graft survival and attainment of insulin independence in subjects with T1D who underwent ITx.We conducted a retrospective cohort study on 47 ITx recipients from 2000 to 2018.Islet infusion was performed via intrahepatic portal (n=44) or onto the omentum via laparoscopic approach (n=3). Immunosuppression involved anti-IL2 receptor antibody, anti-TNF, and dual combinations of sirolimus, tacrolimus, or mycophenolate mofetil (Edmontonlike) in 38 subjects (80.9%). T-cell depletion induction with Edmonton-like maintenance was used in 9 subjects (19%). GAD65 and IA2 autoantibodies were assessed pre-transplant and post-transplant (monthly) until graft failure, and categorized as persistently negative, persistently positive, or seroconverters. Graft survival was analyzed using U-Mann-Whitney test, and Quade's nonparametric ANCOVA adjusted for confounders. Kaplan-Meier and Log-Rank tests were employed to analyze attainment of insulin independence. P value <0.05 indicated statistical significance.Results: ITx recipients with persistent autoantibody negativity (n = 21) showed longer graft function (98 [61 -182] months) than those with persistent autoantibody positivity (n = 18; 38 [13 -163] months), even after adjusting for immunosuppressive induction protocol (P = 0.027). Seroconverters (n=8) had a median graft survival time of 73 (7.7 -167) months, which did not significantly differ from the other 2 groups. Subjects with persistently single antibody positivity to GAD65 (n = 8) had shorter graft survival compared to negative islet autoantibody (GAD65/IA2) subjects (n = 21; P = 0.016). Time of graft survival did not differ in subjects with single antibody positivity to IA2. The proportion of insulin independence attainment was similar irrespective of autoantibody status.